Features of the vegetative state and arterial pressure level in children with chronic gastroduodenal pathology - T. M. Mikhieieva; D. Yu. Nechytailo; V. V. Poniuk; T. P. Fomina (Zaporožskij Medicinskij Žurnal)
Abstract